The evaluation of quality of learning of industrial development and training centre (ppkpi) jakarta using kirkpatrick method - Essada Nurachmah, Asri; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2019)
Abstract. In order to enhance the level of social welfare, Indonesia is working hard to create many job opportunities for its citizens as well as Government of Jakarta. PPKPI as a subsidiary of Bureau of Labor and Transmigration Jakarta Province has a vision and mission that related to Governor and mission to be a Centre of Excellence by becoming a training centre for Jakarta citizens and its surrounding before entering working society and compete with other workforce. However, in doing the program, PPKPI faced an issue that might be an obstacle to measure how effective and good the quality of the alumni after finish the program. The feedback issue from all stakeholders including students, alumni, and users are not in the maximum level that makes PPKPI faced difficulty to measure its training program. The Kirkpatrick method about four level of evaluation of training program is designed to identify the issue that appeared in PPKPI by assessing reaction, learning, behavior, and result level to the all stakeholders in PPKPI. The objective of this research is to create an evaluation system or procedures with purpose to prove that PPKPI programs impact positively to the community as its vision. This research focused on questions how the condition of current evaluation system is, what issues that came up from the root cause, and what solution that is being proposed to improve the training development program. From the findings done by interview and secondary data, the trainees in PPKPI already competent in hard skill however, they are still loose job opportunity due to lack of interview skill, etc. The solution to PPKPI for improving the quality of learning during training program are procuring general basic course including Focus Group Discussion (FGD) done by alumni and user, trial of psychological test to acknowledge trainees, and new concept of collecting the feedback. By doing those activities, PPKPI shall gain quality of learning during training program that reflects to the its vision to be a Centre of Excellence.Keywords: Training Development, Learning Quality, Kirkpatrick Four Levels of Evaluating Training Program, Jakarta Government, Social Welfare.